CELL-MEDIATED IMMUNE RESPONSE TO ENTOMOPATHOGENIC FUNGUS Beauveria bassiana IN DIFFERENT STRAINS OF SILKWORM Bombyx mori L. - PRAVEENA, M. SHEEBA; SAVITHRI, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Mulberry silkworm Bombyx mori is a tiny insect with great economic and scientific significance. Silkworms are delicate and susceptible to different groups of pathogenic microorganisms such as bacterial, protozoan, viral and fungal pathogens due to continuous domestication for centuries. Disease occurrence is the main reason for not achieving the potential yield parameters of silkworm cocoon crops. Silkworm is the best model to assess the immune mechanism in insects and possesses a well-organized and competent immune system that eliminates different types of invading pathogenic microorganisms to protect the body from infection. The immune system in silkworm Bombyx mori mainly comprises of cellular immunity and humoural immunity. The cellular immunity is mediated by different types of haemocytes viz., prohaemocytes, plasmatocytes, granulocytes, spherulocytes and oenocytoids resides in the haemolymph of silkworm Bombyx mori. Humoral reactions require several hours for full expression while cellular interactions are immediate and direct between haemocytes and the invading pathogens that include phagocytosis, nodulation and encapsulation. Dynamics of total and differential haemocyte count designate the degree of tolerance/resistance of the host system to infections and can be used as a catalogue for diagnosis of the disease. Therefore, the investigation was carried out with the following objective To examine the cellular immune-potency in silkworm Bombyx mori during the progress of fungal pathogen Beauveria bassiana by quantifying the density of total and differential haemocytes in three popular silkworm hybrids viz., double hybrid (CSR2 x CSR27) x (CSR6 x CSR 26), crossbreed (PM x CSR2) and bivoltine single hybrid (CSR2 x CSR4) compared to healthy silkworms.